Emergence and reproductive rhythms of Ephestia kuehniella (Lepidoptera Pyralidae) - Xu, J.; Wang, Q.; He, X.Z. (New Zealand Plant Protection, 2008)
Mediterranean flour moth Ephestia kuehniella is a cosmopolitan pest of stored products and its eggs are widely used to rear parasitoids and predators for biological control programmes The laboratory investigations of circadian rhythms and lifespan patterns described in this paper have shown that females had significantly shorter developmental duration from egg to adult than males Emergence occurred throughout the 24 h cycle in both sexes with a peak at dusk Mating mainly occurred during scotophase and peaked on the emergence day while oviposition peaked 1 day after emergence Calling courtship and mating peaked in the second half of scotophase and oviposition peaked at the start of scotophase Permanently paired insects mated up to 3 times with an average of 2 013 matings Dissection of dead females showed the number of spermatophores in the bursa copulatrix equalled the number of observed matings